Keanekeragaman Tumbuhan yang diperjual-belikan di Nurseri Kranggan, Bekasi, Jawa Barat - Silalahi, Marina; Sihotang, Hotmaulina (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2019)
Nursery is a places for buying, selling transactions and plants care in the urban. This study aims to reveal the diversity of plants that are traded in the Kranggan nursery, Bekasi, West Java. This research was conducted by surveying and interviewing nursery owners and managers to find out the types of plants being traded. Reponden was determined by purvosif sampling with criteria namely having a nursery of at least 100 m2 or having worked at the nursery for at least 2 years. The data obtained was analyzed descriptively statistically. Plants that are traded in Kranggan nursery vary greatly between one trader and another, namely between 93-140 species of plants. A total of a total of 197 plants were traded in the Kranggan nursery which were included in 158 genera and 76 families. When viewed from the habitus, most of the traded plants (86 species) are herbs, followed by trees (69 species), shrubs (36 species) and lianas (6 species). Mango (Mangifera indica), klengkeng (Euphoria longana), guava (Psidium guajava), are plants very potential to be developed because its favored by buyer. Bonsai plants such as anting putri (Wrightia religiosa) and Korean banyan (Ficus campanulata) have great economic and conservation potential because it has a high selling price and high fruiting frequency.